Tantangan Dalam Penerapan Manajemen PAK Terhadap Peserta Didik Generasi Alpha - Jinta Fitri Lestari (STT INDONESIA MANADO, 2026)
Abstract: Generation Alpha is a group of learners born since 2010 and growing up in a digital environment that influences their learning methods, thinking patterns, and the formation of values and character. These conditions present new challenges in the implementation of Christian Religious Education (CRE) management, especially when conventional learning approaches can no longer accommodate the characteristics of the digital generation. This research aims to analyze various challenges in the implementation of Christian Religious Education (CRE) management for Generation Alpha students. The study employs a qualitative approach with a literature review method thru critical analysis of theological literature, Christian education, educational management, and studies on Generation Alpha. The research findings indicate that the main challenges include the low internalization of spiritual values due to the dominance of digital media, the digital competency gap among educators, and the suboptimal management of learning that is adaptive to the characteristics of the students. This research concludes that the implementation of PAK management needs to be directed toward the development of contextual, integrative, and technology-based learning strategies, without neglecting the formation of faith, Christian character, and spiritual maturity of Alpha generation students. Abstrak: Generasi Alpha merupakan kelompok peserta didik yang lahir sejak tahun 2010 dan bertumbuh dalam lingkungan digital yang memengaruhi cara belajar, pola berpikir, serta pembentukan nilai dan karakter. Kondisi tersebut menghadirkan tantangan baru dalam penerapan manajemen Pendidikan Agama Kristen (PAK), terutama ketika pendekatan pembelajaran konvensional tidak lagi mampu mengakomodasi karakteristik generasi digital. Penelitian ini bertujuan menganalisis berbagai tantangan dalam penerapan manajemen PAK terhadap peserta didik generasi Alpha. Penelitian menggunakan pendekatan kualitatif dengan metode studi pustaka melalui analisis kritis terhadap literatur teologi, pendidikan Kristen, manajemen pendidikan, dan kajian tentang generasi Alpha. Hasil penelitian menunjukkan bahwa tantangan utama meliputi rendahnya internalisasi nilai spiritual akibat dominasi media digital, kesenjangan kompetensi digital pendidik, serta belum optimalnya pengelolaan pembelajaran yang adaptif terhadap karakteristik peserta didik. Penelitian ini menyimpulkan bahwa penerapan manajemen PAK perlu diarahkan pada pengembangan strategi pembelajaran yang kontekstual, integratif, dan berbasis teknologi, tanpa mengabaikan pembentukan iman, karakter Kristiani, serta kedewasaan spiritual peserta didik generasi Alpha.